STEWART, J. (2021). Hegel ́s Century. Alienation and Recognition in a Time of Revolution. Cambridge: Cambridge University Press. - Aguiriano Benéitez, Mario (Daimon Revista Internacional de Filosofia, 2025)
Reseña de STEWART, J. (2021). Hegel ́s Century. Alienation and Recognition in a Time of Revolution., Cambridge: Cambridge University Press.